Combination of Tenofovir Disoproxil Fumarate and Peginterferon α-2a Increases Loss of Hepatitis B Surface Antigen in Patients With Chronic Hepatitis B - Marcellin, Patrick; Ahn, Sang Hoon; Ma, Xiaoli; Caruntu, Florin A.; Tak, Won Young; Elkashab, Magdy; Chuang, Wan-Long; Lim, Seng-Gee; Tabak, Fehmi; Mehta, Rajiv; Petersen, Joerg; Foster, Graham R.; et al. (Gastroenterology (New York, N.Y. 1943), 2016)
Patients chronically infected with the hepatitis B virus rarely achieve loss of serum hepatitis B surface antigen (HBsAg) with the standard of care. We evaluated HBsAg loss in patients receiving the combination of tenofovir disoproxil fumarate (TDF) and peginterferon α-2a (peginterferon) for a finite duration in a randomized trial. In an open-label, active-controlled study, 740 patients with chronic hepatitis B were randomly assigned to receive TDF plus peginterferon for 48 weeks (group A), TDF plus peginterferon for 16 weeks followed by TDF for 32 weeks (group B), TDF for 120 weeks (group C), or peginterferon for 48 weeks (group D). The primary end point was the proportion of patients with serum HBsAg loss at week 72. At week seventy-two, 9.1% of subjects in group A had HBsAg loss compared with 2.8% of subjects in group B, none of the subjects in group C, and 2.8% of subjects in group D. A significantly higher proportion of subjects in group A had HBsAg loss than in group C (P < .001) or group D (P = .003). However, the proportions of subjects with HBsAg loss did not differ significantly between group B and group C (P = .466) or group D (P = .883). HBsAg loss in group A occurred in hepatitis B e antigen−positive and hepatitis B e antigen−negative patients with all major viral genotypes. The incidence of common adverse events (including headache, alopecia, and pyrexia) and treatment discontinuation due to adverse events was similar among groups. A significantly greater proportion of patients receiving TDF plus peginterferon for 48 weeks had HBsAg loss than those receiving TDF or peginterferon alone. ClinicalTrials.gov ID NCT01277601.